(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Nosteroidal anti-inflammatory drugs (NSAIDs) are a group of pharmaceutical drugs that are commonly used in medicine to stop various inflammatory processes, relieve pain, reduce fever, and prevent thrombosis. To understand the mechanism of action of anti-inflammatory drugs, it is necessary to understand the features of the course of inflammatory processes in the body. Currently, the group of drugs known as NSAIDs includes about 50 original drugs. These drugs can be classified by their chemical structure into several groups, including salicylic acid derivatives, indole derivatives, heteroarylacetic compounds, propionic derivatives, enolic acids, pyrazolone derivatives, coxibs and others. Despite some differences in the chemical structure and features of each group, all these NSAIDs have common pharmacological properties. However, these drugs also have common side effects. They can cause damage to the gastrointestinal tract (gastritis, gastric ulcer and duodenal ulcer), kidney dysfunction, inhibition of platelet aggregation and others.